Design of auditorium in sport facilities - Duško Kuzović (University of Banja Luka, Faculty of physical education and sport, 2018)
Auditorium is an important element for the correct perception of events in the sports field. Many elements influence the quality of the auditorium: the perception of the sports field, the maximum / minimum distance of the viewing, the speed and size of the ball, etc. The relationship between the theater and the sport field must be carefully established. It is necessary to prevent spectators entering in the field, and spectators injures. In practice, three forms of auditorium - sports field separation are applied: perimeter fence, trenches, change of floor level. Before the design process starts, it is necessary to define: the visibility of the sport field, the capacity of the auditorium, the minimum/maximum viewing distance, the type of seats, the level of seating comfort, the competition category seating standards, the structure of the seats, etc. The aim of the paper is to analyze the individual elements of the auditorium. The result of the work should increase the quality of design service, and satisfaction of the spectators of the sports facility.